Ifo World Economic Survey November 2003 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2003)
World Economic Climate: World Economic Climate considerably improved; Economic Expectations: Economic expectations for the next six months are optimistic, current economic situation close to satisfactory; Inflation: Inflation remains moderate; Interest Rates: Expected turnaround in interest rates; Currencies: Euro still seen as overvalued; Special Topic: Spam affects prospects for legitimate marketing
Keywords: 330